One step forward, two steps back: transitions between home, pre-primary and primary education in rural India - Alcott, Benjamin; Banerji, Manjistha; Bhattacharjea, Suman; Nanda, Mansi; Ramanujan, Purnima (Taylor & Francis, 2020)
A growing evidence base highlights the value of high-quality early childhood education (ECE) to children’s cognitive and social development. However, far less is known about how families and children, especially in developing countries, participate in ECE or how these participation patterns reflect families’ thinking and decision-making. This paper utilises a mixed-methods approach to analyse longitudinal household survey and interview data (on 7336 and 180 children, respectively) from the India Early Childhood Education Impact study. Our results indicate that children’s participation trajectories in the early years (age four to eight) do not reflect the age or grade norms specified by national educational policies. And, far from being linear, children’s educational pathways entail considerable back and forth between home, preschool and school. The authors argue that these trajectories reflect both poor implementation of national norms as well as an inadequate understanding among both parents and service providers of how best to support young children’s cognitive development.
Keywords: 3903 Education Systems; 3904 Specialist Studies In Education; 39 Education; Behavioral and Social Science; Basic Behavioral and Social Science; Pediatric Research Initiative; Clinical Research; 4 Quality Education